Pengaruh Terpaan Konten Instagram @Jajansolo terhadap Minat Beli Kuliner di Kota Surakarta bagi Mahasiswa Ilmu Komunikasi Universitas Muhammadiyah Surakarta - Fatra, Alfan Wahida; Santoso, Budi (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
This study aims to analyze the effect of exposure to @Jajansolo Instagram content on culinary buying interest in Surakarta City for communication science students at Universitas Muhammadiyah Surakarta. This research is a type of quantitative research. The independent variable (X) in this study is @Jajansolo Instagram content and the dependent variable (Y) is culinary buying interest in FKI UMS students. The population in this research is communication science students at Universitas Muhammadiyah Surakarta. The technique used in determining the sample in this study uses purposive sampling technique because it is considered suitable with the respondent's criteria that must be met. Based on the results of the calculation of the Yamane formula, the number of samples obtained was 110 respondents. The data analysis technique in this study uses Validity Test, Reliability Test, Normality Test, Linearity Test, Simple Linear Regression Test, T Test, and F Test. The result of this study is that there is a relationship between exposure to @jajansolo insatgram content (X) and culinary buying interest (Y). The coefficient test results after the rcount is known to be 0.877, then next to find out how much influence variable X has on the value of variable Y using the coefficient of determination. So it can be concluded that there is an influence of variable X on Y by 77% and the remaining 23% is influenced by other factors not examined. The F test results show a significance value of 0.000 which is smaller than the significance value of 0.05. It can be obtained that the regression model obtained in this study is feasible to be used to predict the variables in this study. The t test results show that the t value is greater than the t table and the significance value of 0.000 is smaller than the value of 0.05 and has a positive direction. Then the Ho hypothesis is rejected and H1 is accepted in this study. This means that Instagram content (X) @jajansolo has a positive and significant effect on buying interest (Y) culinary on UMS Communication Science Students.